(untitled) (Research, Society and Development, 2022)
Reinforced concrete structures are subject to several forms of deterioration, the main one being the corrosion of the metallic reinforcement that causes social and economic damages, especially in regions with high environmental aggressiveness. Therefore, several countries have studied the feasibility of using non-metallic reinforcement, such as fiber reinforced polymers (FRP). In this context, the present work carried out a theoretical and numerical study of the behavior of concrete beams reinforced with glass fiber reinforced polymer bars (GFRP), carbon (CFRP) and aramid (AFRP), in comparison with a reinforced concrete beam. with steel bars. For the same load, the concrete beam with steel bars was designed according to ABNT NBR 6118:2014, and the reinforced concrete beams with FRP bars according to ACI 440.1R:2015. Then, they were numerically simulated in the ANSYS® software to analyze the stresses, strains and displacements. Finally, it was found that the beam with steel bars required a lower useful design height and the beam with CFRP bars required a smaller area of flexural reinforcement. In numerical simulations, all beams showed consistent behavior according to ABNT NBR 6118:2014 and ACI 318:2011, with the beam composed of concrete and steel showing superior numerical responses in relation to the others. In general, the beams reinforced with FRP obtained satisfactory results compared to the beam reinforced with steel bars, where the beam reinforced with CFRP achieved the best results among the beams with fiber reinforced polymer bars.